Sledování vrstvy sítnicových nervových vláken u glaukomu. II. Stav vrstvy nervových vláken sítnice a vývoj zmĕn zorného pole. Prospektivní studie - Kraus, H; Bartosová, L; Hycl, J; Kondrová, J; Moravcová, Z; Stránská, L (Ceska a slovenska oftalmologie, 2000)
PURPOSE: To determine whether retinal nerve fiber layer (RNFL) photographs can predict future glaucoma visual field damage. METHODS: In a prospective study 158 red free photographs of the RNFL were made from November 1994 to June 1995. 28 eyes of 19 patients with ocular hypertension (repeated intraocular pressure over 21 mmHg and normal visual fields--Peristat 433 Rodenstock--at first examination) could be re-examined for an average time of 42.3 (SD 4.5) months. RESULTS: Only in one eye with normal RNFL at the first examination typical glaucoma visual field defects appeared (6%), but in 6 of 12 eyes (50%) with photographically demonstrable RNFL defects. The difference was statistically significant. CONCLUSION: There is only a minor probability, that visual field defects would appear during 3-5 years in eyes with normal RNFL photographs (6%), but about 50% of eyes with originally found RNFL defects.
Keywords: oční hypertenze; glaukom; Humans; zraková pole; lidé středního věku; Female; Aged; dospělí; Glaucoma; senioři; lidé; retina; Retina; nervová vlákna; Adult; ženské pohlaví; Male; Middle Aged; Photography; fotografování; Ocular Hypertension; Nerve Fibers; Visual Fields; mužské pohlaví; prospektivní studie; Prospective Studies